Improvement of Liver Transplantation Outcome by Heme Oxygenase-1-Transduced Bone Marrow Mesenchymal Stem Cells in Rats - Bin Wu; Hong-Li Song; Yang Yang; Ming-Li Yin; Bo-Ya Zhang; Yi Cao; Chong Dong; Zhong-Yang Shen (Stem Cells International)
Bone marrow mesenchymal stem cells (BMMSCs) exert immunosuppressive activity in transplantation, and heme oxygenase-1 (HO-1) enhances their immunomodulatory effects. The aim of this study was to determine whether HO-1-transduced BMMSCs (HO-1/MSCs) improve rat liver transplantation (LTx) outcomes. Orthotopic LTx rejection models were treated with HO-1/MSCs, BMMSCs, HO-1, or normal saline, respectively. Our results showed a significant improvement in survival rates in the HO-1/BMMSCs group compared to the control groups. At all time points, liver function marker levels in the HO-1/MSCs group were significantly lower than in the other three groups; on POD 1, 7, and 14, the degree of rejection and apoptotic cells was significantly less in the HO-1/MSCs group than in the other three groups. Interleukin- (IL-) 10 and transforming growth factor-β levels were significantly increased, while IL-2, IL-6, IL-17, IL-23, tumor necrosis factor-α, and interferon-γ levels were significantly decreased in the HO-1/MSCs group when compared to the other groups. Splenocyte Tregs were significantly increased by HO-1/MSCs compared with controls on POD 3, 5, 7, 10, 14, and 28. Summarily, we provide evidence that HO-1/MSCs improved allogeneic LTx outcomes by attenuating inflammatory responses and acute cellular rejection, as well as enhanced immunomodulatory effects compared with BMMSCs.